2020
DOI: 10.21580/perj.2020.2.2.5087
|View full text |Cite
|
Sign up to set email alerts
|

Uji Efektifitas Dinding Ruangan Panoramik Instalasi Radiologi RSUD Prof. Dr. MA Hanafiah SM Batusangkar Menggunakan TLD-100

Abstract: Research on the effectiveness of panoramic room walls has been carried out in the Radiology Installation of Prof. Dr. MA Hanafiah SM Batusangkar. This study aims to determine the effectiveness of the panoramic room walls in absorbing radiation emitted by panoramic aircraft, as well as knowing the safety level of the room around the panoramic inspection room in accordance with the dose limit values of workers and the general public. This type of research is a quantitative research by taking direct measurements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(2 reference statements)
0
1
0
1
Order By: Relevance
“…From the discussion above, it can be concluded that concrete or lightweight concrete (hebel) coated with lead (Pb) can be used as a radiation shielding material. Concrete with a minimum thickness of 20 cm should be given a lead coating of 2 mm, so that it is able to withstand radiation and does not cause negative effects on the health of patients and radiation workers [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Aircraft Medical X-rays Generalmentioning
confidence: 99%
“…From the discussion above, it can be concluded that concrete or lightweight concrete (hebel) coated with lead (Pb) can be used as a radiation shielding material. Concrete with a minimum thickness of 20 cm should be given a lead coating of 2 mm, so that it is able to withstand radiation and does not cause negative effects on the health of patients and radiation workers [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Aircraft Medical X-rays Generalmentioning
confidence: 99%
“…Untuk itu diperlukan suatu pengukuran paparan radiasi hambur di dalam ruangan dan di sekitar ruangan pesawat sinar-X dan perhitungan nilai efektifitas penahan atau perisai radiasi yang ada di sekitar ruangan tersebut. Penelitian yang berhubungan dengan efektifitas penahan radiasi juga pernah dilakukan dengan mengukur paparan radiasi menggunakan TLD 100 untuk radiasi sebelum dan setelah menembus dinding ruang panoramik kurang dari 90% dan kurang efektif dalam menahan radiasi [8]. Penelitian lain memperlihatkan bahwa faktor eksposi juga mempengaruhi paparan radiasi dimana semakin tinggi faktor eksposinya maka semakin besar jumlah paparan radiasinya, jarak titik aman yang direkomendasikan untuk pasien diruang ICU > 3 meter dengan menggunakan kV rendah [9].…”
unclassified